An explanation of the mystifying bakanae disease narrative for tomorrow's rice - Shakeel, Qaiser; Mubeen, Mustansar; Sohail, Muhammad Aamir; Ali, Sajjad; Iftikhar, Yasir; Tahir Bajwa, Rabia; Aqueel, Muhammad Anjum; Upadhyay, Sudhir K.; Divvela, Praveen Kumar; Zhou, Lei (Frontiers in Microbiology, 2023)
Rice production is severely hampered by the bakanae disease (Fusarium fujikuroi), formerly recognized as Fusarium moniliforme. F. moniliforme was called the F. fujikuroi species complex (FFSC) because it was later discovered that it had some separate species. The FFSC's constituents are also well recognized for producing phytohormones, which include auxins, cytokinin, and gibberellins (GAs). The normal symptoms of bakanae disease in rice are exacerbated by GAs. The members of the FFSC are responsible for the production of fumonisin (FUM), fusarins, fusaric acid, moniliformin, and beauvericin. These are harmful to both human and animal health. This disease is common around the world and causes significant yield losses. Numerous secondary metabolites, including the plant hormone gibberellin, which causes classic bakanae symptoms, are produced by F. fujikuroi. The strategies for managing bakanae, including the utilization of host resistance, chemical compounds, biocontrol agents, natural goods, and physical approaches, have been reviewed in this study. Bakanae disease is still not entirely preventable, despite the adoption of many different tactics that have been used to manage it. The benefits and drawbacks of these diverse approaches are discussed by the authors. The mechanisms of action of the main fungicides as well as the strategies for resistance to them are outlined. The information compiled in this study will contribute to a better understanding of the bakanae disease and the development of a more effective management plan for it.